2020
DOI: 10.18517/ijaseit.10.1.9770
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Ficus lyrata Warb Fruit Extract and the Effect on Toxicity, Physicochemical, and Microbiology Properties of Chicken Carcass

Abstract: The use of plant extraction as natural and safe preservatives, have been highly recommended for the improvement of the microbiological and sensory quality of food. In the present investigation, the dried fruit of Ficus lyrata Warb was subjected to bio preservative to chicken carcass. This study aimed to characterize the ethyl acetate extract on the phytochemical compound, antioxidant activity, antibacterial activity, to determine the toxicity of the extraction with lethal dose (LD 50) value and to study the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Awan et al (2018) melakukan percobaan menggunakan ekstrak buah F. carica untuk fungsi proteksi jantung terhadap agen-agen kardiotoksik. Wira et al (2020) melakukan uji toksisitas ekstrak buah F. lyrata dalam rangka penggunaannya sebagai antibakteri untuk pengawetan daging ayam. Hingga saat ini kami belum menemukan publikasi mengenai kajian toksisitas maupun penelitian tentang pemanfaatan ekstrak F. hispida.…”
Section: Pembahasanunclassified
“…Awan et al (2018) melakukan percobaan menggunakan ekstrak buah F. carica untuk fungsi proteksi jantung terhadap agen-agen kardiotoksik. Wira et al (2020) melakukan uji toksisitas ekstrak buah F. lyrata dalam rangka penggunaannya sebagai antibakteri untuk pengawetan daging ayam. Hingga saat ini kami belum menemukan publikasi mengenai kajian toksisitas maupun penelitian tentang pemanfaatan ekstrak F. hispida.…”
Section: Pembahasanunclassified
“…Ficus lyrata Warb., commonly known as the fiddle leaf fig, is a species of the Moraceae family known for its ornamental value (Fang et al, 2007). However, beyond its aesthetic appeal, F. lyrata has also been recognised for its potential medicinal properties, including antimicrobial and antioxidant activities (Rizvi et al, 2009;Pękala-Safińska et al, 2019;Wira et al, 2020). Seraia et al (2008) showed that F. lyrata has gas-absorbing and phytoncide properties that can be used to improve the sanitary properties of indoor air.…”
Section: Introductionmentioning
confidence: 99%
“…The roots, bark and stems contain flavonoids, terpenoids, alkaloids, phenolic and tannins, while the fruits and leaf extract of F. lyrata has large quantity of phenolic compounds, tannins, flavonoids and triterpenoids (Zhang et al, 2019). Several studies has shown the presence of phenolic acid conjugates (Ocaffeoyl quinic acid, and gentisic acid) and flavonoids (apigenin and leutolin C glycosides) in significant concentration (Wahyudha et al, 2020). F. lyrata is traditionally used to treat many disorders such as gastrointestinal problems, anthelmintic, diabetes, antitumor activity, asthma, astringent, bleeding, bone fracture, antiseptic, cough, sexual disorders, ear-ache and toothache, migraine, eye troubles, scabies, gonorrhea, paralysis and anti-diarrhea (Haider and Zhong, 2014).…”
Section: Introductionmentioning
confidence: 99%